2017
DOI: 10.1080/13506285.2017.1327466
|View full text |Cite
|
Sign up to set email alerts
|

Face processing is enhanced in the left and upper visual hemi-fields

Abstract: We tested whether two known hemi-field asymmetries would affect visual search with face stimuli. Holistic processing of spatial configurations is better in the left hemi-field, reflecting a right hemisphere specialization, and object recognition is better in the upper visual field, reflecting stronger projections into the ventral stream. Faces tap into holistic processing and object recognition at the same time, which predicts better performance in the left and upper hemifield, respectively. In the first exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 56 publications
2
13
0
Order By: Relevance
“…Results from the dimensional analysis suggest that a reduced LVF bias may be best explained by autistic traits rather than by the level of social anxiety. This result adds to a small number of studies suggesting that autistic traits and social anxiety may have different relations to social attention processes (Capriola-Hall et al, 2018;Kleberg et al, 2017). As noted in the introduction, social anxiety and autism are overlapping symptom dimensions, and a better understanding of their respective relation to atypical social attention may enhance our understanding of both conditions.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Results from the dimensional analysis suggest that a reduced LVF bias may be best explained by autistic traits rather than by the level of social anxiety. This result adds to a small number of studies suggesting that autistic traits and social anxiety may have different relations to social attention processes (Capriola-Hall et al, 2018;Kleberg et al, 2017). As noted in the introduction, social anxiety and autism are overlapping symptom dimensions, and a better understanding of their respective relation to atypical social attention may enhance our understanding of both conditions.…”
Section: Discussionsupporting
confidence: 51%
“…Both autism and SAD are linked to atypical face perception (Chita-Tegmark, 2016; Kleberg et al, 2019). A small number of studies have suggested that the two symptom dimensions may map onto different aspects of face perception (Capriola-Hall et al, 2018;Kleberg et al, 2017) but again, no studies exist in relation to the LVF bias.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the mouth distinguishes between fearful and surprised expressions, enforcing fixation at the brow and thus putting the mouth on the lower vertical meridian did not lead to better emotion classification performance relative to fixation of an eye or cheek (see Figure 5). More generally, a lower visual field advantage for processing task-relevant spatial frequencies is in tension with evidence showing that, for some tasks, including a variety of face perception tasks, there is an upper visual field advantage (e.g., Carlei, Framorando, Burra, & Kerzel, 2017;Hagenbeek & Van Strien, 2002;Quek & Finkbeiner, 2014a;Quek & Finkbeiner, 2014b, 2016, which, for faces and some objects, might be related to their typical visual-field positioning in everyday environments (Kaiser & Cichy, 2018;Kaiser, Quek, Cichy, & Peelen, 2019). Indeed, even isolated face parts (eyes, mouth) are better recognized and more strongly represented in right inferior occipital gyrus when they were presented at typical, rather than reversed, visual field locations (de Haas et al, 2016).…”
Section: Discussionmentioning
confidence: 96%
“…Recognition biases have also been associated with the location of faces in the visual field (Carlei & Kerzel, 2015). Furthermore, using a visual search paradigm to investigate gaze processing, Carlei, Framorando, Burra, and Kerzel (2017) reported upper and left visual field asymmetries (VFAs) that could be enhanced or suppressed by varying specific characteristics of the stimuli presented. This is not surprising since there are important and well-established variations in receptive field size across the retina, cortical magnification factors, and visual acuity, to cite just a few variables (Silva et al., 2018).…”
Section: Introductionmentioning
confidence: 99%